4 - Quand Abidjan était la plaque tournante de l’immigration clandestine africaine vers l’Europe (1960–1975) - Chikouna Cisse; Alassane Diabaté (Afrika Zamani, 2022)
In this article, we try to test the historical regression method so dear to Marc Bloch. It consists of apprehending the past from the evolutions and dynamics of the present. If African irregular migration to Europe nowadays crystallizes interest on a global scale, it is because of the emotional load of the thousands of African deaths in the Mediterranean and elsewhere. We do however propose to go beyond this topicality to focus on the historicity of the phenomenon in Ivory Coast, between 1960 and 1975. The historical reasoning thus has a double objective: to show the centrality of Ivory Coast in post-colonial African mobility according to trajectories and logics in rupture with those of the colonial period; and to underline the antiquity of the phenomenon of African irregular migration to Europe, when during the two decades of post-independence, Abidjan, the Ivorian capital, was one of the hubs.